Research on the Design and Marketing of Online Tourism Planning Platform - Chao, Li-Ping; Fan, Tsu-Yeh; Zhang, Zi-Xuan; Weng, Yu-Che; Yang, Yi-Xi (Journal of China-ASEAN Studies, 2022)
The biggest issue with group self-guided traveling is that everyone cannot get together to discuss and arrange the entire itinerary. In order to solve this problem, this research uses the evaluation research method through Evernote. Evernote is a collaborative operation platform that links to the cloud platform and uses an App as an interface to enable a collaborative online discussion of a travel itinerary. After the conclusion is drawn, the system will output the itinerary plan and budget table, and various reminder functions can be set afterwards. The cloud platform linked to the system allows users to store and edit images, and supports quick sharing to social networking sites. This research hopes that through the establishment of this platform and the formulation of marketing strategies, consumers can make group travel as an easy task, ensuring good relationships with relatives and friends and creating good memories.